Typologie mondiale des relations ville-port - César Ducruet (Unité Mixte de Recherche 8504 Géographie-cités, 2008)
This paper analyzes city-port relationships on a world scale through the three concepts of centrality, nodality and intermediacy. 330 port cities represent half of the world’s coastal urban population and container traffic volumes. A factor analysis highlights the maritime or urban specializations of the nodes. Results show that beyond a north-south hierarchical structure, profiles are distributed across relatively homogenous regional areas. The typology illustrates the disequilibria of city-port relations in major European port cities, while other regions show a higher city-port interdependence. This world differentiation allows the questioning of a unique model of city-port relationships and, at the same time, provides a better understanding of the spatial and functional principles defining the port city in general.